Research on Multiple Paths and Governance Logic of Office Efficiency Improvement in Universities from the Perspective of Intelligent Transformation - Liu, Xiaona; Wu, Ziling (Education Insights, 2026)
Intelligent transformation has become a core driver for modernizing internal governance and enhancing operational efficiency in higher education institutions. Grounded in the objective of optimizing administrative efficiency, this study employs the Technology–Organization–Environment (TOE) analytical framework to explore the mechanisms through which intelligent technologies reshape the synergy between administrative management and teaching services. The research identifies three key dimensions in which intelligent empowerment enhances institutional efficiency: transitioning from process automation to intelligent decision-making, evolving from information silos to collaborative sharing, and upgrading from reactive responses to proactive, demand-oriented services. On this basis, the study constructs a multi-dimensional collaborative framework that integrates intelligent administrative systems, refined teaching management, and holistic faculty–student services. It further elaborates concrete implementation strategies for process reengineering, precision evaluation, and service innovation, emphasizing data-driven workflow optimization and evidence-based decision support. In addition, safeguard mechanisms are proposed across three dimensions: data security protection, organizational culture transformation, and performance evaluation feedback, thereby ensuring sustainable and controllable intelligent transformation. By systematically clarifying the governance logic and multiple paths of office efficiency improvement, this research provides theoretical foundations and practical guidance for universities seeking to overcome governance bottlenecks, reduce administrative redundancy, and build smart, efficient, and secure modern administrative ecosystems aligned with the strategic goals of digital higher education.